Pedagogical workshops for good nursing practices in the care of people with chronic pain (Revista Científica Integrada, 2025)
Objective: To report the experience of in-service continuing education workshops for nurses working in the care of people with chronic pain in primary health care. Method: Between August and October 2022, workshops were held focusing on the topics of "clinical reasoning," "use of ICNP®," and "evidence-based care for people with chronic pain."Experience report: The sessions encouraged critical discussions about nursing diagnoses, the need for structured records, and the importance of standardized terminologies, which enhance communication and improve the quality of care. Problem-posing methodologies enabled the identification of the topics addressed with real-world challenges. Final considerations: The results reinforce the value of continuing education and evidence-based practice in nursing. It is hoped that future work will adopt the methodologies used in this study to improve continuing education in various healthcare settings.
Keywords: Continuing education; Problem-based learning; Chronic pain; Standardized nursing terminology